2020
DOI: 10.1038/s41419-020-02902-2
|View full text |Cite
|
Sign up to set email alerts
|

Homoharringtonine suppresses tumor proliferation and migration by regulating EphB4-mediated β-catenin loss in hepatocellular carcinoma

Abstract: Overexpressed EphB4 conduce to tumor development and is regarded as a potential anticancer target. Homoharringtonine (HHT) has been approved for hematologic malignancies treatment, but its effect on hepatocellular carcinoma (HCC) has not been studied. This study elucidated HHT could restrain the proliferation and migration of HCC via an EphB4/β-catenindependent manner. We found that the antiproliferative activity of HHT in HCC cells and tumor xenograft was closely related to EphB4 expression. In HepG2, Hep3B a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…In recent years, HHT has also been used in research on various solid tumors, such as bladder, kidney, lung, and colorectal cancer [21][22][23][24]. Recent studies have reported that HHT suppresses tumor proliferation and migration by regulating EphB4--catenin loss in HCC [25]. In this study, we also observed the inhibitory effect of HHT on the growth and metastasis of HCC in vivo and in vitro.…”
supporting
confidence: 60%
“…In recent years, HHT has also been used in research on various solid tumors, such as bladder, kidney, lung, and colorectal cancer [21][22][23][24]. Recent studies have reported that HHT suppresses tumor proliferation and migration by regulating EphB4--catenin loss in HCC [25]. In this study, we also observed the inhibitory effect of HHT on the growth and metastasis of HCC in vivo and in vitro.…”
supporting
confidence: 60%
“…It has been reported that homoharringtonine down-regulates EphB4 expression to mediate phosphorylation and degradation of β-catenin, impairing HCC progression. 115 The trans-chalcone is another anti-tumor agent that can reduce β-catenin expression in impairing proliferation of HCC cells. 116 These examples were provided to show how β-catenin activation and inactivation can affect survival rate and growth of HCC cells and in the next sections, we specifically discussed targeting β-catenin with anti-cancer agents in HCC therapy.…”
Section: Beta-catenin and Hepatocellular Carcinomamentioning
confidence: 99%
“…After three repeats of screening, information on the primary positive candidates was obtained from the KCB. Several chemicals previously known to regulate metastasis signalings were identified, including vinblastine, bufalin, tomatine, homoharringtonine, and mogroside IV [ 16 , 17 , 18 , 19 , 20 ], thus, underscoring the validity of our screening. Cytotoxicity tests were performed using novel candidate chemicals to exclude chemicals that could induce strong cell death.…”
Section: Resultsmentioning
confidence: 62%